ETIKA KOMUNIKASI REMAJA TERHADAP ORANG TUA DITINJAU DARI PSIKOLOGI PERKEMBANGAN REMAJA: (Studi Kasus di Desa Blang Panyang Lhokseumawe) - Fauzan Fauzan; Nazaruddin Nazaruddin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2021)
This research was conducted in the Blang Panyang Village Community, Muara Satu District, Lhokseumawe City. The time of the study was carried out on June 9, 2021. Population and sample, The population in this study was the entire community of Blang Panyang Village, Muara Satu District, Lhokseumawe City and the sample was the youth of Blang Panyang Village, Muara Satu District, Lhokseumawe City. In this study, the author uses a 'qualitative' approach, the research conducted is descriptive. Instruments in this study were interview sheets and documentation. Based on the description of the research results that have been described, it can be concluded that the ethics of adolescent communication with parents in terms of adolescent developmental psychology can go through a process of developing formal operational skills which include: (1) the formation of personal identity; (2) greater personal autonomy; (3) greater ability to relate and communicate with other people, such as children of the same age and the opposite sex; (4) the growth of more complex moral thoughts or morals. The point is that adolescent communication ethics will be well formed if it is supported by the moral guidance of parents at home.